2020
DOI: 10.1002/brb3.1666
|View full text |Cite
|
Sign up to set email alerts
|

An instrument for the evaluation of muscle dysmorphia: The Italian validation of the adonis complex questionnaire

Abstract: Background and aims Muscle dysmorphia (MDM), or bigorexia, is a subcategory of body dysmorphic disorder (BDD), also known as “Adonis Complex” in nonscientific contexts. One of the most used tools to investigate MDM is the Adonis Complex Questionnaire (ACQ). The ACQ is a 13‐item US questionnaire, designed for male subjects only, related to the dissatisfaction and concerns about physical appearance. The aim of the current study was to evaluate the validity of the Italian version of the ACQ. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The interest in the subject of the risk of eating disorders in men is constantly growing. (Głębocka, 2009;Riccobono, 2020;Badenes-Ribera et al, 2019) showed, inter alia, that attempts of gaining weight during adolescence are increasing triple. However, the most disturbing fact is that the majority of men who wish to gain weight and muscle mass are within the normal BMI range.…”
Section: Discussionmentioning
confidence: 99%
“…The interest in the subject of the risk of eating disorders in men is constantly growing. (Głębocka, 2009;Riccobono, 2020;Badenes-Ribera et al, 2019) showed, inter alia, that attempts of gaining weight during adolescence are increasing triple. However, the most disturbing fact is that the majority of men who wish to gain weight and muscle mass are within the normal BMI range.…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature has studied the correlation between exercise abuse, MD, appearance anxiety, and compulsive behavior [ 36 , 40 ]. Findings have suggested a high risk of exercise abuse and body image disorders in recreational exercisers that used fitness products under no supervision [ 36 , 37 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Moreover, they have informed that changes in habits, such as radical diets and the use of SS, have been reported as risk factors of MD, exercise abuse, and addictive behaviors in exercisers [ 34 , 35 , 36 , 38 , 39 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…Findings have suggested a high risk of exercise abuse and body image disorders in recreational exercisers that used fitness products under no supervision [ 36 , 37 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Moreover, they have informed that changes in habits, such as radical diets and the use of SS, have been reported as risk factors of MD, exercise abuse, and addictive behaviors in exercisers [ 34 , 35 , 36 , 38 , 39 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. Therefore, authors have reported users of SS with high levels of SM, MD and exercise abuse which are vulnerable to a risky intake that may lead to physical and mental problems [ 36 , 37 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations